2017
DOI: 10.1177/1071100717739670
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesia Using Peripheral Anesthetic Block of the Foot and Ankle

Abstract: Level I, high-quality prospective randomized clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
(14 reference statements)
1
5
0
Order By: Relevance
“…For this study however, different risk factors were selected because national health care and economic unemployment support are guaranteed, so socioeconomic status is not a problem. Consistent with the literature [ 46 ], we did not observe anaesthesia complications, supporting the use of regional anaesthesia, which has several advantages including improved patient satisfaction, faster mobilisation, reduced length of hospital stay and reduced used of opioids [ 41 , 57 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For this study however, different risk factors were selected because national health care and economic unemployment support are guaranteed, so socioeconomic status is not a problem. Consistent with the literature [ 46 ], we did not observe anaesthesia complications, supporting the use of regional anaesthesia, which has several advantages including improved patient satisfaction, faster mobilisation, reduced length of hospital stay and reduced used of opioids [ 41 , 57 ].…”
Section: Discussionsupporting
confidence: 90%
“…The impact of risk factors and the type of anaesthesia ( femoral-sciatic versus ankle block ) on pain, pain during movement, satisfaction and quality of life was also analysed, finding that the block type does not have any influence on clinical outcomes. Many studies have compared ankle blocks to more proximal blocks [ 42 , 44 , 45 ] or compared the analgesic efficacy of an ankle block in addition to general anaesthesia or spinal anaesthesia [ 46 , 47 ]. Only one study, by Tharwa et al, compared the efficacy and safety of ankle block versus sciatic-saphenous nerve block in 42 patients with HV having undergone surgery [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of our multivariable analysis also showed that prescription amount was the only independently significant influencing factor on opioid consumption. Gupta et al, 17 as well Stefani et al, 30 demonstrated the importance of regional anesthesia after foot and ankle surgeries and reported lower pain scores and lower narcotic use for up to 56 days after surgery with an improved pain intensity during the immediate postoperative period. Presumably, patients who received a peripheral block were undergoing more significant surgeries and, therefore, were prescribed more pain medication on the assumption that the procedure would be more painful.…”
Section: Discussionmentioning
confidence: 98%
“…In a prospective, randomized study of 57 patients undergoing foot and ankle surgery with spinal anesthesia with or without ankle block, patients who received an ankle block reported both a lower mean postoperative pain score and a longer onset to pain after surgery. 85…”
Section: Impact Of Coadministered Therapies On Outcomes Of Spinal Ane...mentioning
confidence: 99%
“…In a prospective, randomized study of 57 patients undergoing foot and ankle surgery with spinal anesthesia with or without ankle block, patients who received an ankle block reported both a lower mean postoperative pain score and a longer onset to pain after surgery. 85 In the context of hip fracture surgery, preoperative femoral nerve block or fascia iliaca compartment block may also aid positioning for the performance of spinal anesthesia. Femoral nerve blockade, performed before spinal anesthesia, in patients undergoing hip fracture surgery can be performed as a single shot block immediately preoperatively or as a continuous catheter technique several hours or even days in advance of surgery.…”
Section: Peripheral Nerve Blockadementioning
confidence: 99%